2008
DOI: 10.1111/j.1526-4637.2007.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining Patient-Centered, Multidimensional Success Criteria for Treatment of Chronic Spine Pain

Abstract: Objective. This study aimed to define patient-determined success criteria for treatment of chronic spine pain across four domains: pain, fatigue, emotional distress, and interference with daily activities.Patients. Seventy chronic spine pain patients were recruited from university-affiliated pain clinics.Design. The study design was longitudinal, with pretreatment and post-treatment assessments. Post-treatment assessment occurred approximately 2 months after treatment initiation.Outcome Measures. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 15 publications
5
40
0
Order By: Relevance
“…Patients’ success criteria were shown to require a larger reduction in pain, distress, and fatigue than originally hypothesized, though patients did not expect to reach their own success criteria for the level of interference domain 5. Similarly, research has shown that, to consider treatment for pain successful, patients’ criteria for treatment outcome are relatively high compared with health care professionals’ criteria 6,7…”
Section: Introductionmentioning
confidence: 90%
“…Patients’ success criteria were shown to require a larger reduction in pain, distress, and fatigue than originally hypothesized, though patients did not expect to reach their own success criteria for the level of interference domain 5. Similarly, research has shown that, to consider treatment for pain successful, patients’ criteria for treatment outcome are relatively high compared with health care professionals’ criteria 6,7…”
Section: Introductionmentioning
confidence: 90%
“…81 Most of these also suffer from a list of chronic psychosocial problems. [82][83][84] These in turn interfere with the outcome of treatment. 85 Negative beliefs about pain 86 and depression 87 seem to be predictors of higher levels of disability.…”
Section: Other Issues More Important Than the Causes Of Back Pain?mentioning
confidence: 97%
“…Individuals with NP regard reduced fatigue, secondary to pain relief, as the most important indicator of treatment success (Brown et al, 2008; Robinson et al, 2005). Although it is estimated that up to 55% of persons with chronic pain experience fatigue, it is a symptom that often receives little attention in clinical practice (Mota & Pimenta, 2006).…”
mentioning
confidence: 99%